The Key to Mental Health: Social and Semantic Domain Analysis of Sesoken in Matthew 9:22 - Julius Stefanus Sibagariang (Jurnal Pendidikan Agama Kristen (JUPAK), 2025)
Mental health is an important issue and is one way to achieve a golden Indonesia in 2045. However, in Indonesia, the issue has not received much attention. The authors in this study try to discuss mental health by linking it to the health of faith. The authors found that having healthy faith is the key to mental health. Through social analysis of Matthew 9:20-22, it can be seen that the story of the bleeding woman is about mental health. Even though she is experiencing very heavy suffering, a bleeding woman can still have mental health because of the faith she has. The healthy faith that she has already has a big impact on her mental health. This is clearly seen through Jesus' expression towards her, "...your faith has saved you..." (Matt. 9:22). The word "save" in the text apparently has various translations. Through semantic domain analysis of the words "save” or “sesoken", it turns out that they contain the meaning "to heal". In this way, through social and semantic domain analysis of the word “sesoken” in Matthew 9:22, it becomes clear that healthy faith is the key to mental health.